Entrepreneurship among university graduates - Bjorn Harsman; Zara Daghbayshian (European Regional Science Association (ERSA), 2010)
Entrepreneurship among university graduates The aim of the paper is to shed light upon entrepreneurship among university graduates. We are interested in differences across educational areas and among universities regarding entrepreneurial selection and performance. The paper differs from similar studies in two respects. In order to broaden the common definitions used to measure entrepreneurship we suggest a typology making it possible to differentiate between full-time and part-time entrepreneurs as well as between full-time and part-time employees. Secondly, we differentiate between both level of education, area of education and university of graduation. In order to capture some of the uncertainties related to the choice among our entrepreneurial categories we use individual time series income data. Using cross-section data on all Swedish graduates we examine the impact of university on entrepreneurial choice and performance for graduates of 44 Swedish universities. A separate analysis is done for graduates of 5 education fields to control for heterogeneity of education. The results suggest that entrepreneurial preferences differ by educational fields, that graduates of some universities are more entrepreneurial than others. We also find that the preferences for different entrepreneurial occupations differ across universities. As to the university effect on graduates' earnings we find significant university effect for only a small group of universities, which differ by field of education and entrepreneurial category.
Keywords: 330